The (in)elasticity of moral ignorance - Marta Serra-Garcia; Nora Szech (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate the elasticity of moral ignorance with respect to monetary incentives and social norm information. We propose that individuals suffer from higher moral costs when rejecting a certain donation, and thus pay for moral ignorance. Consistent with our model, we find significant willingness to pay for ignorance, which we calibrate against morally neutral benchmark treatments. We show that the demand curve for moral ignorance exhibits a sharp kink, of about 50 percent, when moving from small negative to small positive monetary incentives. By contrast, while social norms strongly favor information acquisition, they have little impact on curbing moral ignorance.
Keywords: D83; D91; C91; 330; information avoidance; morality; unethical behavior; social norms